Masdar-nāme-yi Türkī’deki İsimlerin Tematik Söz Varlığı - Kaman, Sevda (Fatih Sultan Mehmet Vakıf Üniversitesi, 2025)
Hindistan, Afganistan, Pakistan ve Bangladeş’in büyük bir kısmını kapsayan sınırlarıyla kısa zamanda büyüyen Bâbürlü Devletinin Farsça, Arapça, Hintçe, Urduca gibi çeşitli dillerin konuşulduğu kozmopolit bir yapısı vardır. Arapça din dili olarak gücünü korurken 16. yüzyılın sonlarından itibaren Farsça, Bâbürlü Devletinde yönetim, kültür ve güç aracı haline gelmiştir. Devletin kurucusu Bâbür Şah’ın (H. 888/M. 1483- H. 937/ M. 1530) resmî dil tayin ettiği Çağatay Türkçesi yalnızca saray erkânının ve ordunun bildiği yerel dile dönüşmüştür. Bu sebeplerle saray erkânı ve yöneticiler ata dillerinin öğrenilmesi ve korunması için Türkçe dersleri almışlar, Çağatay Türkçesini öğreten sözlük ve gramer kitaplarının yazılmasını teşvik etmişlerdir. Bunlardan biri Mîr Îsâoğlu Hâcı Şâşî’nin I. Bahadır Şah’ın emriyle H. 1090/ M. 1679 yılında yazdığı Masdarnāme- yi Türkī’dir. Çağatay Türkçesi-Farsça olarak iki dilli hazırlanan ve sözlük-gramer niteliği taşıyan eserde isimler sıralanırken kısmi olarak tematik usulden faydalanılmıştır. Çalışmanın birinci bölümünde Masdar-nāme-yi Türkī tanıtılmış; ikinci bölümünde doküman analizi yapılarak eserdeki isimlerin tematik tasnifi ve içerik değerlendirilmesi yapılmıştır. Çalışmanın amacı eserin yazıldığı dönemin gündelik hayatına, kültürel yapısına dair bilgiler içeren söz varlığına ve tematik yapısına dikkati çekmek, Bâbürlü Devleti zamanında yazılan sözlüklerin ortak söz varlığının tespit edilmesine ve bu sözlüklerin tematik yönden karşılaştırılmasına yönelik araştırmalara, sözlükbilim-toplumsal dilbilim çalışmalarına veri sunmaktır.

The Mughal Empire, which rapidly expanded its borders to encompass much of India, Afghanistan, Pakistan, and Bangladesh, possessed a cosmopolitan structure in which a variety of languages - such as Persian, Arabic, Hindi, and Urdu were spoken. While Arabic retained its authority as the language of religion, from the late 16th century onward Persian became a key instrument of administration, culture, and power in the Mughal Empire. Chagatai Turkish, which the founder of the empire, Babur Shah (1483–1530) (AH 888-937), designated as the official language, gradually turned into a vernacular known only by the court elite and the military. In an effort to preserve their ancestral language, court officials and administrators promoted the teaching of Turkish and supported the production of instructional materials such as grammars and dictionaries. One of these is the Masdar-nāme-yi Turkī, written by Mîr Îsâoğlu Hâcı Şâşî in 1090 AH / 1679 CE upon the order of Bahadur Shah I. Prepared bilingually in Chaghatay Turkish and Persian, the work functions as both a dictionary and grammar, and while listing nouns it partially employs a thematic method The first part of the study introduces the Masdar-nāme-yi Turkī, while the second part provides a thematic classification and content analysis of nouns in the work through document analysis.. The aim of the study is to draw attention to the vocabulary and thematic structure of the work, which provides information about the daily life and cultural contex of the period in which the work was written, and to provide data for research on identifying the shared lexicon of dictionaries compiled in the Mughal Empire, comparing these dictionaries thematically, and for lexicoglogical and sociolinguistic studies.
The Thematic Vocabulary of the Nouns in Masdar-nāme-yi Turkī
Keywords: Bâbürlü Devleti; Çağatay Türkçesi; Çağatayca-Farsça Sözlükler; Tematik Sözlük; İsimler; The Mughal Empire; Chagatai Turkish; Chagatai-Persian Dictionaries; Thematic Dictionary; Nouns